Nanoporous water oxidation electrodes with a low loading of laser-deposited Ru/C exhibit enhanced corrosion stability - Haschke, Sandra; Pankin, Dmitrii; Mikhailovskii, Vladimir; Barr, Maïssa K. S.; Both-Engel, Adriana; Manshina, Alina; Bachmann, Julien (Beilstein Journal of Nanotechnology, 2019)
For the oxidation of water to dioxygen, oxide-covered ruthenium metal is known as the most efficient catalyst, however, with limited stability. Herein, we present a strategy for incorporating a Ru/C composite onto a novel nanoporous electrode surface with low noble metal loading and improved stability. The Ru/C is coated on the pore walls of anodic alumina templates in a one-step laser-induced deposition method from Ru3(CO)12 solutions. Scanning electron microscopy proves the presence of a continuous Ru/C layer along the inner pore walls. The amorphous material consists of metallic Ru incorporated in a carbonaceous C matrix as shown by X-ray diffraction combined with Raman and X-ray photoelectron spectroscopies. These porous electrodes reveal enhanced stability during water oxidation as compared to planar samples at pH 4. Finally, their electrocatalytic performance depends on the geometric parameters and is optimized with 13 μm pore length, which yields 2.6 mA cm−2, or 49 A g−1, at η = 0.20 V.
Keywords: electrochemistry; nanostructures; noble metals; ruthenium catalyst; water splitting